The Role of Sex and Compulsory Heterosexuality Within the Rural Methamphetamine Market - Milagros Early, Alessandra (Crime & delinquency, 2024)
Studies of the connection between methamphetamine use and sex have tended to focus on gay men or men who have sex with men. Drawing from semi-structured interviews with 40 cisgender heterosexual women who used methamphetamine in rural Missouri, we investigate the multiple ways in which sex played into their market navigations. Our findings reveal the nuances of sexual agency within patriarchal structural constraints. We use and expand upon a queer criminological framework to investigate the intersecting gendered and sexualized expectations that cisgender heterosexual men imposed on women. Our study reveals how compulsory heterosexuality shapes behavior within the rural methamphetamine market.